The Journey of Humanity and the Keys to Human Progress - Galor, Oded (Dublin Penguin Random House, 2022)
Why are humans the only species to have escaped?only very recently?the subsistence trap, allowing us to enjoy a standard of living that vastly exceeds all others? And why have we progressed so unequally around the world, resulting in the great disparities between nations that exist today? Galor?s gripping narrative explains how technology, population size, and adaptation led to a stunning ?phase change? in the human story a mere two hundred years ago. But by tracing that same journey back in time and peeling away the layers of influence?colonialism, political institutions, societal structure, culture?he arrives also at an explanation of inequality?s ultimate causes: those ancestral populations that enjoyed fruitful geographical characteristics and rich diversity were set on the path to prosperity, while those that lacked it were disadvantaged in ways still echo today.
Includes index